Pediatric Cortical Vein Thrombosis: Frequency and Association With Venous Infarction. Issue 3 (March 2016) - Ritchey, Zak; Hollatz, Amanda L.; Weitzenkamp, David; Fenton, Laura Z.; Maxwell, Emily C.; Bernard, Timothy J.; Stence, Nicholas V.
Abstract : Background and Purpose—: Cortical vein thrombosis (CVT) is an uncommon site of involvement in cerebral sinovenous thrombosis. Few reports have described pediatric CVT, and none has differentiated its unique attributes. This study assessed the clinical features and radiographic outcome of a cohort of children with cerebral sinovenous thrombosis, comparing those with CVT to those without CVT. Methods—: Children diagnosed with cerebral sinovenous thrombosis were retrospectively reviewed and separated into 2 groups based on the presence or absence of cortical vein involvement. Results—: Fifty patients met inclusion criteria, including 12 with CVT. The CVT group was more likely to present with seizure ( P =0.0271), altered mental status ( P =0.0271), and a family history of clotting disorder ( P =0.0477). Acute imaging of the CVT group more commonly demonstrated concurrent superior sagittal sinus thrombosis ( P =0.0024), parenchymal hemorrhage ( P =0.0141), and restricted diffusion ( P <0.0001). At follow-up, the CVT group more commonly showed headache, seizure, and focal neurological deficit ( P =0.0449), and venous infarction ( P =0.0007). Conclusions—: In our cohort, CVT was significantly associated with seizures at presentation, hemorrhage and restricted diffusion on acute imaging, as well as neurological disability and venous infarction at follow-up. Involvement of cortical veins in cerebral sinovenous thrombosis is associated with an increased risk of infarction and adverse outcome in children. Abstract : Supplemental Digital Content is available in the text.